Optimizing ChatGPT as a Means of Digital Literacy for 21st Century Students - Sofyan, Anas; Hasan, Munawir; Maftuhah (Institut Studi Islam Muhammadiyah Pacitan, 2026)
The era of artificial intelligence (AI) presents challenges as well as opportunities for the development of 21st century student literacy. ChatGPT as a form of generative AI can be used as a digital literacy medium that is able to facilitate access to information, expand insights, and foster a reading culture. This article aims to analyze reading habituation strategies by utilizing ChatGPT optimally and identify opportunities and risks that arise in the context of academic literacy. The research method used is qualitative descriptive with a case study approach through interviews with students and lecturers. The results of the discussion show that ChatGPT can function as a literacy facilitator, especially as an entrance to understanding initial concepts before students deepen with credible academic reading. However, there are risks such as dependence, low information verification, and reduced critical thinking skills when used passively. Therefore, the optimization of ChatGPT must be directed at critical, evaluative, and creative reading habits so that students are able to develop digital literacy competencies in a balanced manner. In conclusion, reading habituation by utilizing ChatGPT in the AI era can be an effective strategy to form a literacy generation that is productive, adaptive, and ready to face the challenges of the 21st century.